On coefficients of edge domination polynomial of a graph. (3rd March 2016) - Chaluvaraju, B.; Chaitra, V.
Abstract: An edge domination polynomial of a graph G is the polynomial where d e ( G, t ) is the number of edge dominating sets of G of cardinality t . In this paper, we provide tables which contain coefficient of edge domination polynomial of path and cycle. Also, certain properties of edge dominating polynomial are given.